Impact of Drp1-Mediated Mitochondrial Dynamics on T Cell Immune Modulation - Song, Jun; Yi, Xiaofang; Gao, Ruolin; Sun, Li; Wu, Zhixuan; Zhang, Shuling; Huang, Letian; Han, Chengbo; Ma, Jietao (Frontiers in Immunology, 2022)
In recent years, various breakthroughs have been made in tumor immunotherapy that have contributed to prolonging the survival of tumor patients. However, only a subset of patients responds to immunotherapy, which limits its use. One reason for this is that the tumor microenvironment (TME) hinders the migration and infiltration of T cells and affects their continuous functioning, resulting in an exhausted phenotype. Therefore, clarifying the mechanism by which T cells become exhausted is of significant for improving the efficacy of immunotherapy. Several recent studies have shown that mitochondrial dynamics play an important role in the immune surveillance function of T cells. Dynamin-related protein 1 (Drp1) is a key protein that mediates mitochondrial fission and maintains the mitochondrial dynamic network. Drp1 regulates various activities of T cells in vivo by mediating the activation of a series of pathways. In addition, abnormal mitochondrial dynamics were observed in exhausted T cells in the TME. As a potential target for immunotherapy, in this review, we describe in detail how Drp1 regulates various physiological functions of T cells and induces changes in mitochondrial dynamics in the TME, providing a theoretical basis for further research.